If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7x + 7) = 189 Reorder the terms: 3(7 + 7x) = 189 (7 * 3 + 7x * 3) = 189 (21 + 21x) = 189 Solving 21 + 21x = 189 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 21x = 189 + -21 Combine like terms: 21 + -21 = 0 0 + 21x = 189 + -21 21x = 189 + -21 Combine like terms: 189 + -21 = 168 21x = 168 Divide each side by '21'. x = 8 Simplifying x = 8
| 8x-16=9x+8 | | 3x+2=x+40 | | 3(3-6x)=-117 | | -1=-(1-4x)+x | | 6(4x+10)=324 | | 3x+15x+150=0 | | 9/2a-5=-1 | | 18-(x+3)-2x=4+(x-5) | | 7+7x=3x+47 | | 5+(-15d+1)=2(7d-16)-d | | -4+p=-2 | | (3x+5)(x-6)=5x+10 | | -2(-3+7x)=6 | | 24x-3=45 | | -5n-5(n-7)=32-7n | | -5x-4=92+3x | | -12x+8=-2 | | x(2-7)=20 | | -2x+6=-60+4x | | -12+8=-2 | | 9+4x-17=12 | | 3x+185=180 | | 3x/7=-4/9 | | -10+x=-6x-80 | | 4m+3m+8=12 | | 5x43/10 | | 14=x-3x-4 | | 2x+90+x+95=180 | | 5t-1=t/3-17 | | -4+(-2+1)+5-(3-(1-2)+4)+1-2= | | 12X=4X-60 | | 4z/7-5=10 |